Dimensional retention of photocured ceramic units during 3D printing and sintering processes. Issue 8 (15th April 2021) - Zhang, Cheng; Luo, Zhongqiang; Liu, Chengbo; Zhu, Junyi; Cao, Jiwei; Yuan, Jingkun; Wang, Pei; Liu, Changyong; Lao, Changshi; Chen, Zhangwei
Abstract: In this study, photocuring-based digital light processing (DLP) 3D-printing technology was used to prepare basic photocuring units from cordierite ceramic slurries loaded with three different average particle sizes. Exposure time was varied to realize a range of ultraviolet light-energy dosages. Basic units, including single lines, apertures, and single walls, were printed with different feature dimensions such as single-line width and thickness, aperture diameter, and single-wall thickness. The morphologies and structures of the units were studied after printing and sintering. Their dimensions were measured, and the relative and absolute differences before and after each processing step were calculated. The dimension-retention levels were finally determined and analyzed across the ranges of slurries, exposure times, and designed dimensions. Detailed insights into the printing and sintering behaviors and performances of the ceramic slurries and printed units were gained. This study contributes to the understanding and analysis of potential dimensional errors and the printed and sintered quality of ceramic components prepared based on photocuring-based DLP 3D printing.